An ecological overview of Prosopis pallida, one of the most adapted dryland species to extreme climate events - Salazar Zarzosa P. (2021)
Financial support was provided by the Peruvian program CONCYTEC (163-2018-FONDECYT-BM-IADT-SE) granted to Dr. Pablo Salazar. RV was supported by the Spanish MEC project DIVERBOS ( CGL2011- 30285-C02-02 ) and ECO-MEDIT ( CGL2014-53236-R ), the project Ecología funcional de los bosques andaluces y predicciones sobre sus cambios futuros (For-Change) (UCO-27943) by Junta de Andalucía (Spain) , the project Funcionalidad y servicios ecosistémicos de los bosques andaluces y normarroquíes: relaciones con la diversidad vegetal y edáfica ante el cambio climático by Junta de Andalucía (Spain), all co-funded with European FEDER funds. RMNC was supported by the ISOPINE (UCO-1265298), ESPECTRAMED (CGL2017-86161-R) and SilvAdapt RED2018 102719 T projects. GML was supported by the Deutsche Forschungsgemeinschaft (DFG, ME 5087/1-1).